2021
DOI: 10.1016/j.ssmph.2021.100879
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative research about public health risk perceptions on ambient air pollution. A review study

Abstract: Background Understanding public health risk perceptions is essential in efficient environmental health management. In the light of the negative impact of air pollution on health and the direct and indirect mediation of this impact through risk perceptions, it is crucial to better understand the lay perceptions of air pollution. Since qualitative research methods are well suited for this aim, the central objective of this study is to present a review of qualitative research articles in the field of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 37 publications
2
48
0
Order By: Relevance
“…Participants also suggested that they tend not to dwell on the impacts of pollution to health as they ultimately feel little control over their exposure to air pollution. A review of qualitative research into health perceptions of air pollution since the 2000s found that the link between air pollution and human health is not always obvious from a lay perspective (Noël, Vanroelen, & Gadeyne, 2021 ). This may explain the broadly held awareness of air pollution but lack of direct concern for health, which is particularly apparent where individuals feel there is little they can do to mitigate the risk (Bickerstaff & Walker, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Participants also suggested that they tend not to dwell on the impacts of pollution to health as they ultimately feel little control over their exposure to air pollution. A review of qualitative research into health perceptions of air pollution since the 2000s found that the link between air pollution and human health is not always obvious from a lay perspective (Noël, Vanroelen, & Gadeyne, 2021 ). This may explain the broadly held awareness of air pollution but lack of direct concern for health, which is particularly apparent where individuals feel there is little they can do to mitigate the risk (Bickerstaff & Walker, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term exposure to air pollution will seriously reduce people’s subjective well-being [ 64 ]. The perception of environmental pollution may be more obvious than socialization and cultural factors in influencing people’s attitudes and reactions to the environment [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…, 2013). Such issues have increased people's health risk perceptions (Noël et al. , 2021) and negative emotions leading to anxiety and depression (Gu et al.…”
Section: Literature Reviewmentioning
confidence: 99%